Akuntabilitas Pengelolaan Dana Desa - Mita Ayu Kristini; Dwi Iga Luhsasi; Bambang Ismanto (Wahana: Jurnal Ekonomi, Manajemen dan Akuntansi, 2020)
This study aims to find about village funds management which focuses on administration and reporting in Bendungan Village, Pabelan District, Semarang Regency in the 2018 budget year. The research method used is qualitative with descriptive type. Data collection techniques are done by observation, interview and documentation. Analysis of the data used according to Miles and Huberman was done interactively and survived to completion. The activities of analyzing qualitative data are data reduction, data presentation, and drawing conclusions. The results showed that the Bendungan Village Government had applied 5 principles recommended by the United Nations Development Program (UNDP), namely transparency, controllability, liability, responsiveness, and responsibility in management the village fund. However, the village head must improve his performance in reporting on the APBDesa Implementation Report in a timely manner.